Nursing Competency Test Guidance Training For Nursing Students In The Nursing Department By Implementing The Ruang Ukom Application - Dini Rudini; Fadliyana Ekawaty; Andika Sulistiawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The National Nursing Competency Examination (UKOM) is a crucial requirement for obtaining a Registration Certificate (STR) for professional nursing practice in Indonesia. Despite its importance, many nursing students face challenges in preparing for the exam, particularly in understanding case-based questions, applying critical thinking, and accessing effective learning support. This community service program aimed to improve students’ readiness for UKOM by implementing a digital-based training and guidance strategy using the Ruang Ukom application at the Nursing Department of Jambi University. A blended learning approach was employed, combining face-to-face sessions, small group mentoring, and independent practice using the application. The Ruang Ukom platform featured interactive case-based questions, real-time feedback, exam simulations, and learning progress tracking. A total of 86 students participated, divided into intervention and mentoring groups. Quantitative analysis showed a significant increase in knowledge scores, with the mean pre-test score of 104.84 rising to 160.22 in the post-test. The intervention also enhanced students’ confidence, exam readiness, and critical thinking skills. The program encouraged digital transformation in academic guidance and demonstrated that integrating technology into nursing education can effectively support competency development. This model has potential for broader application and sustainability in preparing future nursing graduates for professional certification.